The Relationship Between Speed And Agility Towards The Ability To Dribble The Ball In Football Games Of Students At Inpres 12/79 Gattareng Elementary School - Yoyo Prianto; Alif Aryadi Hardi; Khalid Rijaluddin (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2026)
This study aims to determine the relationship between speed and agility towards dribbling skills in football games for students of Inpres 12/79 Gattareng Elementary School. The type used in this study is correlation research. The population in this study were 124 students of Inpres 12/79 Gattareng Elementary School. The sample in this study was 30 students using a purposive sampling technique. This research instrument used a 30-meter running test, Agility T-test, and dribbling test. Data analysis used statistical analysis with the help of a computer through the SPSS program. The results of the study showed that there was a significant relationship between speed and dribbling ability with a sig value of 0.005, there was a significant relationship between agility and dribbling ability with a sig value of 0.009, and there was a significant relationship between speed and agility together with dribbling ability with a sig value of 0.011. Keywords: Speed; Agility; Dribble; Football.